Targeting protein inactivation through an oligomerization chain reaction - Contegno, Francesco (The National Academy of Sciences, 2002)
A general strategy for inactivation of target proteins is presented, which we have termed “oligomerization chain reaction.” This technique is based on the fusion of the self-associating coiled-coil (CC) domain of the nuclear factor promyelocytic leukemia (PML) to target proteins that are able to self-associate naturally. Oligomerization through the CC region of promyelocytic leukemia, and through the natural self-associating domain, triggers the oligomerization chain reaction, leading to formation of large molecular weight complexes and functional inactivation of the target. As a test case, we have chosen the oncosuppressor p53, naturally occurring as a tetramer. Fusion of the CC to p53 leads to formation of stable high molecular weight complexes—as shown by size exclusion chromatography—to which wild-type p53 is recruited with high efficiency. CC-p53 chimeras delocalize wild-type p53 to the cytoplasm and inhibit its transcriptional regulatory properties, resulting in a loss of p53 function. We propose that this strategy may be of general application to self-associating factors and represent a complementary approach to currently used functional inactivation-based strategies.